2014
DOI: 10.18632/oncotarget.3211
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from bone marrow mesenchymal stem/stromal cells transport tumor regulatory microRNA, proteins, and metabolites

Abstract: Human mesenchymal stem/stromal cells (hMSCs) have been shown to support breast cancer cell proliferation and metastasis, partly through their secretome. hMSCs have a remarkable ability to survive for long periods under stress, and their secretome is tumor supportive. In this study, we have characterized the cargo of extracellular vesicular (EV) fraction (that is in the size range of 40-150nm) of serum deprived hMSCs (SD-MSCs). Next Generation Sequencing assays were used to identify small RNA secreted in the EV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
266
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(278 citation statements)
references
References 62 publications
7
266
1
Order By: Relevance
“…Also, MSCs tend to home to injured tissues, and some of the EVs they produce may retain this homing ability. In addition, MSCs are an attractive source of EVs because of an unusual property of the cells: They can survive for weeks in culture with medium containing no protein or growth factors but continue to produce EVs (47)(48)(49)(50). During incubation of MSCs from bone marrow in α-MEM, the cultures underwent selection with survival of a subpopulation that expressed genes characteristic of embryonic cells (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, MSCs tend to home to injured tissues, and some of the EVs they produce may retain this homing ability. In addition, MSCs are an attractive source of EVs because of an unusual property of the cells: They can survive for weeks in culture with medium containing no protein or growth factors but continue to produce EVs (47)(48)(49)(50). During incubation of MSCs from bone marrow in α-MEM, the cultures underwent selection with survival of a subpopulation that expressed genes characteristic of embryonic cells (47).…”
Section: Discussionmentioning
confidence: 99%
“…During incubation of MSCs from bone marrow in α-MEM, the cultures underwent selection with survival of a subpopulation that expressed genes characteristic of embryonic cells (47). Pochampally and coworkers subsequently demonstrated that the MSCs incubated in α-MEM produced EVs, and they extensively characterized the EVs (48). They also demonstrated that the EVs supported tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes transfer their cargo miRNAs to recipient cells (120,121) and MSC-derived exosomes contain more than 700 miRNAs that are bound to argonaute2 (AGO2), a component of the RNAinduced silencing complex (RISC) (122,123). The effect of engineered MSC-derived exosomes that carry elevated miRNAs on brain remodeling after stroke has been investigated in vitro and in vivo (118,119).…”
Section: Hsc-exosomes and Therapiesmentioning
confidence: 99%
“…These metastatic OS cells secrete both an active soluble form and an exosome-encapsulated form of uPA to drive the migration or metastatic conversion of OS cells [139]. Other research demonstrated that exosomes secreted by human MSCs could exhibit antiapoptotic function or cell-protective function to increase OS survival under serum starvation conditions [140]. Exosomes may also be a neo-drug vector for OS treatment.…”
Section: Emerging Role: Exosomesmentioning
confidence: 99%